Phospholipid inhibitors - Galli, M. (Hämostaseologie, 2011)
The antiphospholipid syndrome (APS) is defined by the association of arterial and/or venous thrombosis and/or pregnancy complications with the presence of at least one among the main antiphospholipid antibodies (aPL) (i. e., Lupus anticoagulants, LA, IgG and/ or IgM anticardiolipin antibodies, aCL, IgG and/or IgM antiβ2-glycoprotein I antibodies, aβ2-GPI). Several clinical studies have consistently reported that LA is a stronger risk factor for both arterial and venous thrombosis compared to aCL and aβ2-GPI. In particular, LA activity dependent on the first domain of β2-GPI and triple aPL positivity are associated with the risk of thrombosis and obstetrical complications.Asymptomatic aPL-positive subjects do not require primary thromboprophylaxis. Venous thromboembolism is the most common initial clinical manifestation of APS. To prevent its recurrence indefinite anticoagulation is recommended. Long duration treatment with warfarin or aspirin is used after a first cerebral arterial thrombosis. Low molecular weight heparin (LMWH) with or without aspirin is recommended to reduce the rate of obstetrical complications of APS pregnant women.
Keywords: Antiphospholipid syndrome; thrombosis; abortion; antiphospholipid antibodies